PAYROLL ACCOUNTING INFORMATION SYSTEM DESIGN USING MICROSOFT ACCESS AND VISUAL BASIC 6.0 AT RAMLI COLLECTION IN GRESIK REGENCY - Syarifah, Zukhay Lailatus; Zuraidah, Zuraidah (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2023)
Accounting information systems are very important for the development of the company. Very tight competition in the business world requires companies to have good information systems. One of them is the payroll accounting information system. The existence of a payroll accounting information system can help companies to process payroll properly and correctly. The manual payroll process is good, but it's better if you use an application or computerized basis. This study aims to design a payroll accounting information system using Microsoft Access and Visual Basic 6.0 on the Ramli Collection. This research uses a qualitative approach with a qualitative descriptive research type. There are two subjects of this research. Data was collected by means of observation and interviews. Data analysis aims to simplify the data obtained. Data analysis was applied through four stages, namely data collection, data reduction, data presentation, and drawing conclusions. The results of the study show that the Ramli Collection does not yet have a correct accounting information system and is still done manually. There are payroll functions, payroll elements, and payroll documents and records that are not in accordance with payroll theory. Then the results of this study the authors recommend designing payroll systems and programming payroll applications using MicrosoftAccess and Visual Basic 6.0. The results of the study show that the Ramli Collection does not yet have a correct accounting information system and is still done manually. There are payroll functions, payroll elements, and payroll documents and records that are not in accordance with payroll theory. Then the results of this study the authors recommend designing payroll systems and programming payroll applications using Microsoft Access and Visual Basic 6.0. The results of the study show that the Ramli Collection does not yet have a correct accounting information system and is still done manually. There are payroll functions, payroll elements, and payroll documents and records that are not in accordance with payroll theory. Then the results of this study the authors recommend designing payroll systems and programming payroll applications using Microsoft Access and Visual Basic 6.0